Solow Versus Harrod-Domar : Reexamining the Aid Costs of the First Millennium Development Goal - Dalgaard, Carl-Johan.; Erickson, Lennart (Washington, D.C. : International Monetary Fund, 2006)
The First Millennium Development Goal (MDG#1) is to cut the fraction of global population living on less than one dollar per day in half, by 2015. Foreign aid financed investments may contribute to the attainment of this goal. But how much can aid be reasonably expected to accomplish? A widespread calibration approach to answering this question is to employ the so-called development planning technique, which has the Harrod-Domar growth model at its base. Two particularly problematic assumptions in this sort of analysis are the absence of diminishing returns to capital input and an infinite speed of adjustment to steady state after a shock to the economy. We remove both of these assumptions by employing a Solow model as an organizing framework for an otherwise similar analysis. We find that in order to successfully meet the MDG#1 in the context of the currently proposed aid flows, these flows will have to be accompanied by either an acceleration in the underlying productivity growth rate or a major boost to domestic savings and investment in sub-Saharan Africa. In the absence of such changes in the economic environment, the MDG#1 is unlikely to be reached.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet